2020
DOI: 10.1128/mbio.03202-19
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Aspergillus fumigatus Virulence through Targeted Dysregulation of the Conidiation Pathway

Abstract: Inhalation of conidia of the opportunistic mold Aspergillus fumigatus by immunocompromised hosts can lead to invasive pulmonary disease. Inhaled conidia that escape immune defenses germinate to form filamentous hyphae that invade lung tissues. Conidiation rarely occurs during invasive infection of the human host, allowing the bulk of fungal energy to be directed toward vegetative growth. We hypothesized that forced induction of conidiation during infection can suppress A. fumigatus vegetative growth, impairing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 67 publications
1
27
0
Order By: Relevance
“…5A), phenotype (macroscopic or microscopic; Fig. 5B), or virulence (17,(72)(73)(74)(75)(76)(77)(78). In addition, it was reported that 40 g/ml of Dox does not affect the transcriptional profile of S. cerevisiae (79), which contrasts with the broad effect caused by only 1 g/ml Dox on global transcription in human cells (70).…”
Section: Fungal Methionine Synthase In Vivo Target Validationmentioning
confidence: 94%
“…5A), phenotype (macroscopic or microscopic; Fig. 5B), or virulence (17,(72)(73)(74)(75)(76)(77)(78). In addition, it was reported that 40 g/ml of Dox does not affect the transcriptional profile of S. cerevisiae (79), which contrasts with the broad effect caused by only 1 g/ml Dox on global transcription in human cells (70).…”
Section: Fungal Methionine Synthase In Vivo Target Validationmentioning
confidence: 94%
“…For example, the altered in vivo lesions of A. fumigatus H-MORPH colony morphotypes indicate that host morbidity is largely the result of increased inflammatory damage [13]. Similarly, constitutive induction of the asexual development program in A. fumigatus severely attenuates pathogenesis [44].…”
Section: Why Should We Care About Fungal Macroscopic Morphologies?mentioning
confidence: 99%
“…Currently, therapy for disease (such as cancer, autoimmune disease), which based immune escape mechanisms, become increasingly attractive in the biomedical eld. On entry to the host, A. fumigates triggers complex and dynamic interactions with the host [(Stewart et al 2020)]. Besides, after Aspergillus fumigatus invades the host, it can cause a series of mechanisms such as immune recognition, evading immune recognition and resisting host response.…”
Section: Discussionmentioning
confidence: 99%